CREATION OF A THERMAL SHIELD COATING FOR WORK IN EXTREMELY HIGH TEMPERATURES - Елькаді, Махмуд Мохамед Реда Ельсаєд; Лобода, Петро Іванович; Пономарчук, Сергій Георгіович (Problems of Friction and Wear, 2020)
A thermal shield coating (TSC) consisting of carbon fibers, ceramic hollow microspheres and phenol-formaldehyde binder has been created. It is shown that the adding of up to 5% wt of ceramic hollow microspheres makes it possible to obtain a thermal shield coating with a lower density and with the physical and mechanical characteristics at the level of world manufacturers’ analogues. The TSC can be applied on metallic and non-metallic (ceramic, carbon-carbon) products to protect them against thermal degradation.